Finansowe czynniki oraz bariery gospodarki regionalnej i lokalnej w Polsce - Jarosiński, Krzysztof (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2010)
The last twenty years have seen many economic, political and social changes in Poland. Those changes depend on many levels on internal and external conditions. New global relations have stemmed from the world financial crisis. The economic situation is getting worse not only on the leading markets but also on emerging markets including Poland. New barriers and limits have very strong impacts also on local and regional development. These new problems necessitate new methods of analysis and monitoring of economic and social growth. Poland’s current main objective is to verify the public finance sector, especially public expenditures. New finance barriers in Poland could create new troubles for financing many tasks of the public sector, especially of infrastructure and on a social level. Such barriers negatively impact public services on the local and regional levels and may limit expenditures on investment tasks in the future.